2018
DOI: 10.1111/gbb.12485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enriched environment across ages: A study of anhedonia and BDNF gene induction

Abstract: Enriched environment treatment (EET) is a potential intervention for depression by inducing brain-derived neurotrophic factor (BDNF). However, its age dependency remains unclear. We recently found that EET during early-life development (ED) was effective in increasing exploratory activity and anti-despair behavior, particularly in promoter IV-driven BDNF deficient mice (KIV), with the largest BDNF protein induction in the hippocampus and frontal cortex. Here, we further determined age dependency of EET effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 89 publications
3
18
0
Order By: Relevance
“…In line with our previous results [ 24 ], we found reduced mBDNF protein levels, as well as of the pool of the long transcripts of Bdnf in SERT −/− rats with a normalization, due to EE exposure. This perfectly fits the increase in neurotrophin levels after positive environmental stimuli that are often paralleled by improvements at a behavioral level [ 39 , 52 ].…”
Section: Discussionsupporting
confidence: 76%
“…In line with our previous results [ 24 ], we found reduced mBDNF protein levels, as well as of the pool of the long transcripts of Bdnf in SERT −/− rats with a normalization, due to EE exposure. This perfectly fits the increase in neurotrophin levels after positive environmental stimuli that are often paralleled by improvements at a behavioral level [ 39 , 52 ].…”
Section: Discussionsupporting
confidence: 76%
“…To compensate for deficiency of promoter IV‐driven BDNF expression (pIV‐BDNF deficiency), we found that enriched environmental treatment (EET) is more effective than chronic drug treatment with four classes of antidepressants (SSRI: selective serotonin transporter reuptake inhibitor, SNRI: serotonin‐norepinephrine reuptake inhibitor, TCA: tricyclic antidepressant, and MAOI: monoamine oxidase inhibitor) (Jha, Dong, & Sakata, 2011; Sakata, Mastin, et al, 2013). EET, which combines physical exercise, mental stimulation, and social interaction (van Praag, Kempermann, & Gage, 2000), activates almost all other BDNF promoters (Adlard, Perreau, Engesser‐Cesar, & Cotman, 2004; Dong, Xue, & Sakata, 2018; Jha et al, 2011; Russo‐Neustadt, Beard, Huang, & Cotman, 2000; Zajac et al, 2010), whereas the drug treatments activate only a few BDNF promoters (Sakata, 2011; Sakata, Mastin, et al, 2013). EET ameliorate defects caused by BDNF deficiency (Chourbaji et al, 2008; Rossi et al, 2006; Zhu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Though our findings should be considered preliminary due to limited sample size and the cross-sectional nature of our pilot study impedes any causal inferences, it is tempting to speculate about potential mechanisms involved in our findings. Several animal studies show that BDNF deficiency reduces sucrose preference, a loss of sensitivity to reward which has been suggested to model anhedonia (45)(46)(47)(48). Anhedonia is a core symptom of depression, and also plays an essential role in addictive disorders (49,50).…”
Section: Discussionmentioning
confidence: 99%